Mental Workload Analysis Using the NASA-TLX Method in the Engineering Department of PT ABC - Daniel Pardameian Simare Mare; Naufal Affandi; Umalihayati Umalihayati (Universitas KH. Abdul Chalim Mojokerto, 2024)
This study aims to measure and analyze the mental workload of employees in the Engineering department of a manufacturing company using the NASA-TLX method. The goal is to improve employee welfare and company productivity by identifying factors that cause high workloads and finding the right solution. The method used to determine the value of mental workload of employees in the Engineering department, is measured using the NASA-TLX (National Aeronautics and Space Administration Task Load Index) method. This method measures 6 dimensions of workload measurement, namely, Physical Demand, Temporal Demand, Performance, Effort, and Frustration Level. Most Informants (4 out of 5) experience a high mental workload, marked by a score above 60 on the NASA-TLX scale. The dimensions of